#DidacticsRevolution: Applying Kotter’s 8-Step Change Management Model to Residency Didactics - Haas, Mary R. C. (West J Emerg Med, 2020)
INTRODUCTION: Leading change effectively is critical to advancing medical education. Residency didactics often require change in order to meet stakeholder’s needs. Kotter’s change management model (KCMM) is an 8-step method for implementing change that can be applied to educational initiatives. This innovation improved an emergency medicine residency didactics curriculum through application of KCMM. METHODS: An initiative to improve residency didactics curriculum was titled the “Didactics Revolution” and implemented according to KCMM: establish a sense of urgency, form a powerful guiding coalition, create a vision, communicate the vision, empower others to act on the vision, plan for and create short-term wins, consolidate improvements and produce still more change, and institutionalize new approaches. Data from the Annual Program Review was utilized to assess the impact of the KCMM strategy. RESULTS: The percentage of residents who agreed or strongly agreed that lectures provide a valuable learning experience increased from 39.1% in the year prior to 88.0% in the year during the implementation (p < .001), and remained relatively high at 73.5% in the year following. The percentage of residents who agreed or strongly agreed that they felt well-prepared for the written boards increased from 60.9% in the year prior to 92.0% in the year during the implementation (p = .01) and remained high at 73.5% in the year following. CONCLUSION: Residency didactics can be improved through the use of KCMM, a change management model originally developed in the corporate context.